MANUFACTURE OF A DIE PROTOTYPE FOR DIDACTIC PURPOSES IN MECHATRONIC ENGINEERING - MONTIJO-VALENZUELA, ELIEL EDUARDO; DURAN-JIMENEZ , SAUL DANIEL; ALTAMIRANO-RÍOS, LUIS ALBERTO; PÉREZ-GÓMEZ, JOSÉ ISAEL; SALMÓN-AROCHI , OSCAR (Revista de Investigación Académica Sin Frontera: Facultad Interdisciplinaria de Ciencias Económicas Administrativas - Departamento de Ciencias Económico Administrativas-Campus Navojoa, 2020)
The objective of this research is to manufacture a prototype of a teaching die for the specialty of precision mechanical design in mechatronic engineering, in order to achieve the skills required in unit two, regarding dies. The methodology used consists of five stages: 1. Definition of the preliminary conditions. 2. Theoretical calculations for die design. 3. Design, modeling and assembly using computer-aided software (CAD) of the parts that make up the die. 4. Validation with simulation of finite element analysis (AEF). 5. Manufacture of parts and physical assembly of the die. A functional prototype was obtained with which the teacher and student can perform calculations, designs and CAD models, AEF analysis of the static and fatigue type, manufacture of rapid prototypes using 3D printing, the identification of the parts that make up a die and their functioning. The advantage of this prototype, compared to metal die-cutting machines, is its low cost of production and manufacturing, it does not require expensive and specialized machinery for manufacturing, specific designs can be made by the students and its subsequent manufacture within the laboratories of the Technological Institute of Hermosillo.